2023
DOI: 10.2147/ijgm.s406535
|View full text |Cite
|
Sign up to set email alerts
|

Level of Depression and Anxiety on Quality of Life Among Patients Undergoing Hemodialysis

Abstract: Background Despite the growing concern worldwide regarding the quality of life (QoL) and mental well-being among chronic kidney disease (CKD), a few research has been done to address this issue. The study aims to measure depression, anxiety, and QoL prevalence among Jordanian patients with End Stage Renal Disease (ESRD) on hemodialysis and how all of these variables are correlated. Methods This is a cross-sectional, interview-based study on patients at the Jordan Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Furthermore, lots of studies mainly focused on the association between CKD and depression, clinical outcomes and quality of life of the patients with CKD ( Alshelleh et al, 2023 ; Huang et al, 2023 ; Zhu et al, 2023 ), which suggesting that there have been growing concerns on CKD with depression in the last decade. However, researches related to the treatment of CKD in combination with depression remains insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lots of studies mainly focused on the association between CKD and depression, clinical outcomes and quality of life of the patients with CKD ( Alshelleh et al, 2023 ; Huang et al, 2023 ; Zhu et al, 2023 ), which suggesting that there have been growing concerns on CKD with depression in the last decade. However, researches related to the treatment of CKD in combination with depression remains insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a 2023 study by Alshelleh and colleagues in Indonesia found that the majority of participants (92.4%) had depression and 83.3% had generalized anxiety disorder, factors that severely impacted their QoL [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These challenges include grappling with a life-threatening diagnosis, enduring lifelong treatment, navigating various dialysis techniques, and coping with the side effects and complications of treatment. Consequently, the management of CKD and ESRD extends beyond the clinical aspects of the condition, necessitating a holistic approach that prioritizes and maintains the patient’s QoL from diagnosis to EOL care [ 22 ].…”
Section: Symptom Burden and Palliative Care Needs Of Patients Undergo...mentioning
confidence: 99%